Prevalence of work-related musculoskeletal disorders and analysis of working posture using rapid entire body assessment tool amongst the sewing machine operators in a garment industry: a cross sectional study - Kiritkumar, Bosmia Kavita; Pothiraj, Pitchai (International Journal Of Community Medicine And Public Health, 2023)
Background: Work-related musculoskeletal disorders (WMSDs) are emerging problems and it occurs when there is a mismatch between the physical requirements of the job and the physical capacity of the human body. Study aimed to find out the prevalence of WMSDs, the influence of varied working posture and level of physical activity (PA) for the development of WMSDs amongst the sewing machine operators. Methods: This is a cross-sectional study and conducted in a garment industry at Vapi, Gujrat. By purposive sampling technique, 100 sewing machine operators having minimum one year of experience, in the age group of 18-60 years were recruited with their consent. Örebro Musculoskeletal pain questionnaire (ÖMPQ), Rapid Entire Body Assessment tool (REBA), Quick Exposure Check tool (QEC) and International Physical Activity Questionnaire (IPAQ) was administered to all the participants. Data was analyzed using SPSS 24 software. Descriptive statistics applied for categorical variables, Spearman Rank correlation coefficient (r) was calculated for the relationship between PA and WMSDs. Results: This study revealed the prevalence of WMSDs as 70% and low back pain was the commonest complaint. REBA demonstrated that 55% of participants were at high musculoskeletal risk and 44% were at very high risk. QEC identified that neck region had very high exposure risk for the development of WMSDs. The level of PA shows no association with WMSDs (r = 0.040, p=0.62). Conclusions: Sewing machine operators of this study adopted a poor working posture which corresponds to the development of high musculoskeletal risk and an increased prevalence of WMSDs.